Auto-antibodies against gangliosides in patients with Charcot-Marie-Tooth disease. (3rd June 2015) - Catapano, M; Ewart, T; Baker, S
Abstract : Background: In Charcot-Marie Tooth (CMT), vital components of either the myelin sheath or axon are abnormal, slowing nerve conduction and causing functional disability. Recently, there has been speculation the CMT may have an autoimmune component resulting from abnormal protein expression. Methods: Custom autoimmune neuropathy-focused microarray panels were printed in-house using antigens from Sigma, Abnova, Fitzgerald and Matreya according to Cambridge Life Science instructions. Antigens including Myelin Protein Zero, Peripheral Myelin Protein 22, and 20 other well-known gangliosides were tested for IgM and IgG antibodies. Students T-Test and Bonferroni correction factor were used to determine statistical significance between groups and in post-hoc subgroup analysis. Results: Plasma was tested from 17 patients with CMT and 25 young healthy individuals. CMT population consisted of 9 CMT-1a, 1 CMT-1b, 4 CMT-2a, 2 CMT-2f and 2 undetermined CMT type 2 patients. No ganglioside reached statistical significance under a Bonferroni Correction factor (p>0.01) nor were any gangliosides notably raised compared to normal. Sub-group analysis did not reveal theorized peak auto-antibodies levels depending upon their CMT sub-type compared to normal. Conclusions: Although previously shown to have increased auto-antibodies to myelin or axonal proteins, CMT individuals did not demonstrate increased autoantibody levels for the proteins tested at our centre.